2011
DOI: 10.1111/j.1600-0722.2011.00822.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of sleep parameters during contingent electrical stimulation in subjects with jaw muscle activity during sleep: a polysomnographic study

Abstract: There is emerging evidence that feedback techniques based on contingent electrical stimulation (CES) have an inhibitory effect on the electromyogram (EMG) activity of jaw-closing muscles and therefore could be useful in the management of sleep bruxism. This polysomnographic (PSG) study was designed to investigate the effect of CES on PSG parameters in subjects with self-reported bruxism. Fourteen subjects underwent a full PSG investigation in the laboratory for three consecutive nights - one night of adaptatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 45 publications
3
26
0
2
Order By: Relevance
“…Although the present study suggests that the inhibition of SB events with a biofeedback method decreases sleep quality, none of our subjects showed that there was an influence on sleep quality, such as REM, light and deep stages, or nocturnal awakening. Biofeedback is not known to significantly influence sleeping parameters [30]. This finding is consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 95%
“…Although the present study suggests that the inhibition of SB events with a biofeedback method decreases sleep quality, none of our subjects showed that there was an influence on sleep quality, such as REM, light and deep stages, or nocturnal awakening. Biofeedback is not known to significantly influence sleeping parameters [30]. This finding is consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 95%
“…It is based on the principle of CES, where the electrical stimulus applied through the recording electrode evokes an inhibitory response in the active jaw muscle. The device continuously records and analyses the EMG activity and only when the EMG activity exceeds an individually determined threshold, the feedback system will trigger the electrical stimulation [12,18,19].…”
Section: Emg Recordings and Contingent Electrical Stimulationmentioning
confidence: 99%
“…Its purpose is to determine the quality of sleep, frequency of snoring, and tiredness during daytime [12, 15]. Detailed information about the sleep/tiredness/snoring instrument has also been published [8, 12].…”
Section: Questionnairesmentioning
confidence: 99%